Life in space - Rymbu, Galina 1990- (After Hours Editions, 2020)
The immanence of the political / Eugene Ostashevsky -- White bread -- The sleepers -- Life in Space -- Cosmic prospect -- Other poems
Keywords: Rymbu, Galina / 1990- / Poems / Selections; Russian literature / 21st century / Translations into English; Political poetry, Russian / 21st century; Feminist poetry; Political poetry, Russian; Russian literature; Translations; Anthologie